2002
DOI: 10.1051/lait:2002010
|View full text |Cite
|
Sign up to set email alerts
|

Characterisation of lactic starters based on acidification and reduction activities

Abstract: -The acidification and reduction activities of lactic starters have been followed by continuous measurement of the pH and the Eh during the course of milk fermentation. These measurements allowed the calculation of the maximum acidification and reduction rates, and the time, pH and Eh at which these values occurred. Nine strains of Lactococcus sp., 6 strains of Streptococcus thermophilus and 5 strains of Lactobacillus helveticus were studied. In general, the maximum reduction rate of the lactococci was six-fol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

7
48
2
1

Year Published

2006
2006
2013
2013

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 56 publications
(59 citation statements)
references
References 21 publications
7
48
2
1
Order By: Relevance
“…A few studies have reported that the reducing activity of lactic acid bacteria is species dependent and that L. lactis is one of the most reducing lactic acid bacteria (5,8). Also, Jeanson et al (21) showed that the E h of milk drops only after all of the dissolved oxygen is consumed by L. lactis.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…A few studies have reported that the reducing activity of lactic acid bacteria is species dependent and that L. lactis is one of the most reducing lactic acid bacteria (5,8). Also, Jeanson et al (21) showed that the E h of milk drops only after all of the dissolved oxygen is consumed by L. lactis.…”
Section: Discussionmentioning
confidence: 99%
“…The AhpR system may also participate in reduction of oxygen to H 2 O. However, the E h of oxygen-free milk (saturated with nitrogen) is still positive (21), while the E h of milk fermented with L. lactis is close to Ϫ220 mV (8,21). This suggests that, in addition to oxygen, L. lactis reduces other oxidizing compounds present in milk.…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…This value may vary according to the nature of the oxido-reducing molecules in the media. For example, the Nernst factor is 40 mV/pH unit in milk [6].…”
Section: Measurement Of Ehmentioning
confidence: 99%